Optimizing Drilling Efficiency in High-Loss Circulation Zones: A Case Study of Mud Cap and Well Strengthening Techniques in the Ghawar Oil Field (International Journal of Engineering and Computer Science, 2024)
Drilling in high-loss circulation zones is most problematic due to its high NP, risk of well integrity, and increased cost required to manage circulation losses. This research seeks to analyze the implementation of Mud cap and well-bore strengthening in order to enhance the drilling success rates in such reservoirs in Ghawar Oil Field; one of the largest and most productive oil fields globally. The current study evaluates the effectiveness of the above-mentioned techniques in controlling circulation losses as well as stabilizing the wells based on a critical evaluation of the field data including the NPT logs, well stability indices, and cost data recorded in the study area. The studies also reveal that while using both Mud cap and well-bore strengthening methods directly reduced fluid loss, NPT and improved well integrity. Additionally, the analysis gives an appreciation of the cost of each approach and the effects on the general project schedule in the situation where each of the techniques is most suitable to apply. Thus, this research increases the knowledge of best practices in undertaking the high-loss circulation zone drilling and provides recommendations for better efficiency in such geological conditions. The outcomes emphasize on identifying significant zones of operative cost reduction and time gains across the required lifecycle phases, and thus more for enhancing the well integrity management framings intended for the high- loss zones.